PENGARUH MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN PERILAKU HIDUP BERSIH DAN SEHAT MELALUI KEGIATAN “HEALTHY IS FUN” PADA ANAK USIA 5-6 TAHUN” - Afrah Nur Amalina Dalimunthe; Melia Dwi Widayanti; Fatiha Khoirotunnisa Elfahmi; Sri Widayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the project-based learning (PJBL) model on improving clean and healthy living behaviors through the "Healthy Is Fun" activity in children aged 5 to 6 years at Chandra Dimuka PKK Kindergarten. This study began with initial observations that showed that children aged 5-6 years still often choose unhealthy foods and dispose of waste in inappropriate places. This study used a quantitative approach with a single-group pre-posttest design. The subjects of this study consisted of 14 children in group B aged 5-6 years. The data collection technique used an observation table based on two PHBS indicators: choosing healthy and clean snacks and disposing of waste properly. The research procedure consisted of several stages: pretest, treatment, and posttest. The data were analyzed using statistical methods to determine whether there were differences in results before and after treatment. This study showed that there was an increase in clean and healthy living behaviors after using the project-based learning model. Thus, the project-based learning model through the "Healthy Is Fun" activity has a positive impact on improving clean and healthy living behaviors in children aged 5 to 6 years at the Chandra Dimuka PKK Kindergarten.